Pelatihan Publikasi Artikel Pada Jurnal Nasional Terakreditasi - Fitri, Irma; Irma, Ade; Saleh, Habibis; Jelita, Marhama (Jurnal Pengembangan dan Pengabdian Masyarakat Multikultural, 2024)
The community service initiative was initiated after conducting in-depth interviews and widespread questionnaire surveys. These investigations revealed a issue: many educators are unable to get promoted due to their limited proficiency in composing scientific articles. To effectively overcome these issues, it is essential to address them immediately. The main aim of this program is twofold: firstly, to improve educators' comprehension of the functional promotion process, and secondly, to elevate their proficiency in creating scientific articles. The initiative took place in Pekanbaru, involving a group of 16 junior high school teachers Madani. After training program, every participating teacher is now able to skillfully write scientific articles. While these articles have not yet reached the publication stage, it is noteworthy that educators have acquired the essential knowledge and skills necessary for the successful submission of scientific articles to reputable journals and proceedings. The team implementing this service conducted an evaluation to find out teacher perceptions by distributing questionnaires to find out teacher responses regarding the process of writing scientific articles. The results of the evaluation showed that the demands of working hours and other administrative work consumed a lot of time that could have been used by teachers to write. In addition, lack of motivation was also identified as a factor that hinders the process of writing scientific articles.